Monte Carlo studies for the optimisation of the Cherenkov Telescope Array layout - Acharyya, Atreya; Bernlöhr, Konrad; Hinton, James Anthony; Hofmann, Werner; Quirrenbach, Andreas; Rieger, Frank M.; Wagner, Stefan (Astroparticle physics, 2019)
The Cherenkov Telescope Array (CTA) is the major next-generation observatory for ground-based very-high-energy gamma-ray astronomy. It will improve th…
Gesehen am 27.06.2019